Studi Usaha-Usaha Petani dalam Peningkatan Produksi Kelapa Sawit di Desa Alur Manis - Pinem, Kamarlin; Rachmat, Budi (Universitas Negeri Medan, 2015)
This research aims at understanding efforts conducted by farmers to increase palm oil production in their plant, on all of the stages such as selecting the seed, planting, nursing, and capital in production of planting palm oil in Alur Manis Village. The population of the research is all of palm oil farmers amount 50 households in which all of them became sample in collecting data.Â The research uses questionaire and document analyzing as technique in collecting data, while technique of descriptive used in analyzing data. The research shows that selecting for getting prime seed could elevate production of palm oil, and the best time in planting palm oil is in the beginning of rainy season. Whereas nursing should be conducted intensively since during planting to non productive period for earlier production of palm oil. The fertilizing should be conducted in three steps, such following; first step during in period of early age of plant, second step during in grower age of plant, third step during in productive age of plant., with considering maintaining the balance of organic substance of soil. The last that capital in farming positively impact to number of production.